2015
DOI: 10.1017/cem.2015.88
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a physician-nurse supplementary triage assessment team at an academic tertiary care emergency department

Abstract: Objective: The purpose of this study was to evaluate the cost-effectiveness of physician-nurse supplementary triage assistance team (MDRNSTAT) from a hospital and patient perspective.Methods: This was a cost-effectiveness evaluation of a cluster randomized control trial comparing the MDRNSTAT with nurseonly triage in the emergency department (ED) between the hours of 0800 and 1500. Cost was MDRNSTAT salary. Revenue was from Ontario's Pay-for-Results and patient volume-case mix payment programs. The incremental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
11
0
1
Order By: Relevance
“…[35] On the other hand, triage liaison physicians’ (TLPs) role also proposes throughput factors contributed to ED overcrowding. The TLP's role is to work with triage staff to expedite the care of patients based on their medical needs, especially for those with unpredictable waiting times.…”
Section: Resultsmentioning
confidence: 99%
“…[35] On the other hand, triage liaison physicians’ (TLPs) role also proposes throughput factors contributed to ED overcrowding. The TLP's role is to work with triage staff to expedite the care of patients based on their medical needs, especially for those with unpredictable waiting times.…”
Section: Resultsmentioning
confidence: 99%
“…We found an ICER of €31 per ED LOS hour saved, which is probably acceptable for large tertiary care centers with high patient volume. Other authors using the same effectiveness metric for a study of triage in the ED reported ICERs of $3,597.27 ($1,729.47 to infinity) per additional patient seen, $75.37 ($67.99 to $105.30) per physician hour saved, and $112.99 ($74.68 to $251.43) per ED length of stay hour saved 21 . Earlier availability of test results may translate into an unnecessary increase in volume of laboratory testing ordered by emergency physicians during POCT periods and may have contributed to additional costs.…”
Section: Discussionmentioning
confidence: 99%
“…Cost of health interventions includes health services delivery costs such as cost health personnel, investigations, medicines, other health supplies etc. [11][12][13][14][15][16][17][18][19][20] It can also include costs which are not directly related to service delivery, such as the costs of the building and equipment, costs of health facility administration. [11][12][13][14][15][16][17][18][19][20] Next step is to estimate the amount of the resources used in the interventions and value each resource used in monitory terms.…”
Section: Identifying and Valuing Costsmentioning
confidence: 99%